Design and Selection of Marketing Channels for Inti KTP-El Reader at PT Industri Telekomunikasi Indonesia - Noorfazia Indriani, Delvina; Aprianingsih, Atik (The Indonesian Journal of Business Administration, 2016)
Abstract: The KTP-el (Kartu Tanda Penduduk-elektronik) project began in 2009 with a target population of compulsory KTP-el by 172 million. Based on information from the Ministry of Home Affairs, the use of KTP-el card is mandatory in the future and their utilization in various sectors can improve public services. Therefore, it is necessary to have the device for reading the electronic data in the KTP-el card safely and for verifying the validity of the data inside KTP-el card. PT INTI is one of domestic industry that is actively involved in developing and producing the KTP-el reader called â€œINTI KTP-el Readerâ€. This new business is very promising and the investment for this product has been done since mid-2014 and the early planning was to launch this product in 2015. However, due to the product's readiness, the plan cannot be implemented. This product is expected to become one of the products that are ready for sale in mass in 2016 to make up deficiencies in the previous year but until now marketing activities for INTI KTP-el reader have not been done properly. There are two possible ways that company could do in selling INTI KTP-el Reader; direct selling and marketing channels. Marketing channels, also called a trade channel or a distribution channel, are these interdependent organizations involved in the process of marketing a product or services available to end users. Seeing the current situation, the company has few of account executive while the products and projects owned by PT INTI are very diverse. Therefore, things that need to be a particular concern in this research are the appropriate marketing channels strategies that will be very useful for PT INTI. This thesis aims to make design and selection of marketing channels for INTI KTP-el Reader in order to support the successful launch of the product. Analysis of external factors will be done by using PESTEL, Porter's Five Forces and Competitor Analysis. Analysis of internal factors will be done by value chain analysis. Factor affecting channel decision will be analyze by combining intermediary variables, market variables, behavioral variable, product variables and company variables with benchmarking and potential channel member analysis. Result from all variables will be analyzed to find strategy alternatives. Further, the strategy alternatives will be chosen as the proposed recommended strategy based on its importance and urgency. The proposed strategy will be translated into specific action plan to be taken by PT INTI. The selection process of channels, time schedule and resources planning for the action plan will be arranged in order to realize the proposed recommended strategy found in previous analysis.Â Keywords: KTP-el, KTP-el reader, strategy, marketing channels, intermediary.Â